The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1063/1.5054819
|View full text |Cite
|
Sign up to set email alerts
|

Density irregularities, currents, and magnetic fields generated by pulsed local rf heating of a magnetoplasma: Disturbances in rf antenna vicinity

Abstract: The dynamics of narrow, field-aligned magnetoplasma irregularities is studied, which develop under the action of a short rf pulse. The laboratory experiment is aimed at demonstrating the rapid, so-called “unipolar” plasma transport mode, which is accompanied by excitation of eddy currents, in the case of localized rf heating of plasma electrons. The experimental parameters are chosen in a special way. The size of the heating spot, determined by the diameter of the loop antenna, exceeds the electron gyroradius … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Over time, the depth and the length of the density depletion around the heating region increase; the density enhancement travels away from the heating source (Aidakina et al, ). The proportionality between the magnitude of the T e and N e disturbances observed in space as well as the current densities (taken into account the geometrical scales) is good agreement with the quantitative estimates from the laboratory modeling presented by Aidakina et al ().…”
Section: Interpretation Of the Observational Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Over time, the depth and the length of the density depletion around the heating region increase; the density enhancement travels away from the heating source (Aidakina et al, ). The proportionality between the magnitude of the T e and N e disturbances observed in space as well as the current densities (taken into account the geometrical scales) is good agreement with the quantitative estimates from the laboratory modeling presented by Aidakina et al ().…”
Section: Interpretation Of the Observational Resultssupporting
confidence: 87%
“…The possibility of the effects observed by SWARM was previously demonstrated in laboratory experiments. The laboratory modeling performed with KROT plasma facility under the experimental conditions similar to the conditions in the ionosphere, where the plasma irregularities develop under the impact of high‐power HF radio waves, has revealed redistribution of plasma accompanied by electric currents (Aidakina et al, , ; Kostrov et al, ; Starodubtsev et al, ). Because the heated electrons escape along the magnetic field lines, channels with reduced plasma density and enhanced N e above the depletion are formed.…”
Section: Interpretation Of the Observational Resultsmentioning
confidence: 99%
“…Perhaps, this is due to the fact that the active experiment was carried out in the late morning (normally, the daytime ducts were weaker than those in the nighttime using the HAARP and SURA facilities Frolov et al., 2016; Vartanyan et al., 2012), there was a small pump wave power, and the pump wave frequency was almost equal to the critical frequency f 0 F 2 . Note that the effects of the interaction of the irregularities were studied near to and far from the heating source in laboratory experiments on modeling ionospheric heating (Aidakina et al., 2018, 2018a). It was shown that near the heating sources, the irregularities had the form of a set of channels with reduced plasma density and a transient process with a positive density perturbation was observed at a large distance from the heating sources.…”
Section: Results Of the Joint Sura‐norsat‐1 Experimentsmentioning
confidence: 99%
“…laboratory experiments on modeling ionospheric heating (Aidakina et al, 2018(Aidakina et al, , 2018a. It was shown that near the heating sources, the irregularities had the form of a set of channels with reduced plasma density and a transient process with a positive density perturbation was observed at a large distance from the heating sources.…”
Section: 1029/2020gl088462mentioning
confidence: 99%